RESPONSIBILITY FORMATION IN PRIMARY SCHOOL AGE CHILDREN (American Journal of Pedagogical and Educational Research, 2025)
This article emphasizes that it is much more important to form responsibility among younger students. It becomes most relevant from the moment a child enters school. Going to school means a drastic change in the child's entire lifestyle. It says how important responsibility is for a child to obey the rules of behavior and achieve academic results.